iPS Cells—The Triumphs and Tribulations - Riddhi Sharma (Dentistry Journal, 2016)
The year 2006 will be remembered monumentally in science, particularly in the stem cell biology field, for the first instance of generation of induced pluripotent stem cells (iPSCs) from mouse embryonic/adult fibroblasts being reported by Takahashi and Yamanaka. A year later, human iPSCs (hiPSCs) were generated from adult human skin fibroblasts by using quartet of genes, Oct4, Sox2, Klf4, and c-Myc. This revolutionary technology won Yamanaka Nobel Prize in Physiology and Medicine in 2012. Like human embryonic stem cells (hESCs), iPSCs are pluripotent and have the capability for self-renewal. Moreover, complications of immune rejection for therapeutic applications would be greatly eliminated by generating iPSCs from individual patients. This has enabled their use for drug screening/discovery and disease modelling in vitro; and for immunotherapy and regenerative cellular therapies in vivo, paving paths for new therapeutics. Although this breakthrough technology has a huge potential, generation of these unusual cells is still slow, ineffectual, fraught with pitfalls, and unsafe for human use. In this review, I describe how iPSCs are being triumphantly used to lay foundation for a fully functional discipline of regenerative dentistry and medicine, alongside discussing the challenges of translating therapies into clinics. I also discuss their future implications in regenerative dentistry field.